2023
DOI: 10.1002/adfm.202301557
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst‐Support Interactions in Zr2ON2‐Supported IrOx Electrocatalysts to Break the Trade‐Off Relationship Between the Activity and Stability in the Acidic Oxygen Evolution Reaction

Abstract: The development of highly active and durable Ir‐based electrocatalysts for the acidic oxygen evolution reaction (OER) is challenging because of the corrosive anodic conditions. Herein, IrOx/Zr2ON2 electrocatalyst is demonstrated, employing Zr2ON2 as a support material, to overcome the trade‐off between the activity and stability in the OER. Zr2ON2 is selected due to its excellent electrical conductivity and chemical stability, and the fact that it induces strong interactions with IrOx catalysts. As a result, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…82 Additionally, the promotional role of strain on OER activity was reported for the IrO x catalyst on the Zr 2 ON 2 support (IrO x /Zr 2 ON 2 ). 83 This catalyst exhibited a 4.4% tensile-strained surface compared to that of the pure IrO 2 surface (Figure 5h,i). They suggested that the enhancement in the OER activity of the IrO x /Zr 2 ON 2 catalyst was predominantly induced by the reduced oxidation state of Ir due to the tensile strain effect (Figure 5j,k).…”
Section: Enhancing Intrinsic Activitymentioning
confidence: 94%
See 2 more Smart Citations
“…82 Additionally, the promotional role of strain on OER activity was reported for the IrO x catalyst on the Zr 2 ON 2 support (IrO x /Zr 2 ON 2 ). 83 This catalyst exhibited a 4.4% tensile-strained surface compared to that of the pure IrO 2 surface (Figure 5h,i). They suggested that the enhancement in the OER activity of the IrO x /Zr 2 ON 2 catalyst was predominantly induced by the reduced oxidation state of Ir due to the tensile strain effect (Figure 5j,k).…”
Section: Enhancing Intrinsic Activitymentioning
confidence: 94%
“…This impact of lattice strain on the OER activity has been widely investigated in forms of thin film and nanoparticle catalysts. Jiang et al identified the beneficial role of strain in improving OER activity by generating stacking faults in Ru nanoparticles, which exhibited a lower η 10 value of 196 mV compared to the approximately 310 mV of RuO 2 (Figure d–g) . Additionally, the promotional role of strain on OER activity was reported for the IrO x catalyst on the Zr 2 ON 2 support (IrO x /Zr 2 ON 2 ) . This catalyst exhibited a 4.4% tensile-strained surface compared to that of the pure IrO 2 surface (Figure h,i).…”
Section: Design Strategies For Improving Catalytic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the IrO x /Zr 2 ON 2 electrocatalyst exhibits excellent activity and stability in acidic OER. 28 However, the mechanism behind interfacial engineering to promote catalytic reactions by loading active substances on support materials requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al, on the other hand, compared a different support material, such as Zr 2 ON 2 , which has good electrical conductivity, chemical stability, and strong interaction with IrO x catalysts. It was reported that the IrO x /Zr 2 ON 2 electrocatalyst exhibits excellent activity and stability in acidic OER . However, the mechanism behind interfacial engineering to promote catalytic reactions by loading active substances on support materials requires further investigation.…”
Section: Introductionmentioning
confidence: 99%